Normal white matter microstructure in women long‐term recovered from anorexia nervosa: A diffusion tensor imaging study. Issue 1 (9th November 2017) - Bang, Lasse; Rø, Øyvind; Endestad, Tor
Abstract: Objectives: Studies point to white matter (WM) microstructure alterations in both adolescent and adult patients with anorexia nervosa (AN). These include reduced fractional anisotropy in several WM fiber tracts, suggesting reduced WM integrity. The extent to which these alterations are reversible with recovery from AN is unclear. There is a paucity of research investigating the presence of WM microstructure alterations in recovered AN patients, and results are inconsistent. This study aimed to investigate the presence of WM microstructure alterations in women long‐term recovered from AN. Method: Twenty‐one adult women who were recovered from AN for at least 1 year were compared to 21 adult comparison women. Participants were recruited via user‐organizations for eating disorders, local advertisements, and online forums. Diffusion tensor imaging was used to compare WM microstructure between groups. Correlations between WM microstructure and clinical characteristics were also explored. Results: There were no statistically significant between‐group differences in WM microstructure. These null findings remained when employing liberal alpha level thresholds. Furthermore, there were no statistically significant correlations between WM microstructure and clinical characteristics. Discussion: Our findings showed normal WM microstructure in long‐term recovered patients, indicating the alterations observed during the acute phase are reversible. Given the paucity of research and inconsistent findings, future studies are warranted to determine the presence of WM microstructure alterations following recovery from AN.